Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/solr.202000649
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Quasi‐Fermi Level Splitting and Open‐Circuit Voltage Losses in Highly Efficient Nonfullerene Organic Solar Cells

Abstract: The power conversion efficiency (PCE) of state‐of‐the‐art organic solar cells is still limited by significant open‐circuit voltage (VOC) losses, partly due to the excitonic nature of organic materials and partly due to ill‐designed architectures. Thus, quantifying different contributions of the VOC losses is of importance to enable further improvements in the performance of organic solar cells. Herein, the spectroscopic and semiconductor device physics approaches are combined to identify and quantify losses fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 49 publications
4
40
0
Order By: Relevance
“…[280,[286][287][288] The V OC loss associated with surface recombination may be seen to be non-radiative, however, this is a device-related loss as opposed to material-related mechanisms such as non-radiative decay of the CT states discussed in the previous sections. [289] To improve the contacts and reduce surface recombination, electrode interlayers are usually employed. [290][291][292] In this regard, Yao et al demonstrated that the PCE of PM6:Y6 can be increased from 15% to an impressive 17% by changing the cathode interlayer from PDINO to PDNN.…”
Section: Surface Recombination Selectivity and Ohmicity Of The Elecmentioning
confidence: 99%
See 1 more Smart Citation
“…[280,[286][287][288] The V OC loss associated with surface recombination may be seen to be non-radiative, however, this is a device-related loss as opposed to material-related mechanisms such as non-radiative decay of the CT states discussed in the previous sections. [289] To improve the contacts and reduce surface recombination, electrode interlayers are usually employed. [290][291][292] In this regard, Yao et al demonstrated that the PCE of PM6:Y6 can be increased from 15% to an impressive 17% by changing the cathode interlayer from PDINO to PDNN.…”
Section: Surface Recombination Selectivity and Ohmicity Of The Elecmentioning
confidence: 99%
“…[ 280,286–288 ] The V OC loss associated with surface recombination may be seen to be non‐radiative, however, this is a device‐related loss as opposed to material‐related mechanisms such as non‐radiative decay of the CT states discussed in the previous sections. [ 289 ]…”
Section: Fundamental Processes Of Charge Generation and Collectionmentioning
confidence: 99%
“…In this respect, many studies have been conducted in order to reveal the origin of the success of the PM6/Y6 blend OSCs [11][12][13][14][15][16][17][18][19] . However, the photophysical mechanisms underlying efficient free carrier (FC) generation in this blend system remain the subject of continuing debate.…”
Section: Introductionmentioning
confidence: 99%
“…However, the corresponding V OC loss derived from this approach generally includes contributions from both intrinsic bulkrelated processes and surface recombination. In organic solar cells, the presence of surface recombination is usually correlated with electrode-induced photovoltage losses at the contacts [37][38][39], causing a mismatch between V OC and the associated QFLS in the bulk. As such, measurements based on electroluminscence cannot differentiate between intrinsic and electrode-induced photovoltage losses, leading to a consistent underestimation of the QFLS in organic photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%
“…As such, measurements based on electroluminscence cannot differentiate between intrinsic and electrode-induced photovoltage losses, leading to a consistent underestimation of the QFLS in organic photovoltaic devices. A method for overcoming the difficulty in quantifying the QFLS has recently been suggested using photoinduced absorption [39]. However, this method requires detailed knowledge about the absorption cross section and charge-transport parameters of the device, which must necessarily be semitransparent.…”
Section: Introductionmentioning
confidence: 99%